Liver fibrosis in women with chronic hepatitis C: evidence for the negative role of the menopause and steatosis and the potential benefit of hormone replacement therapy. Issue 3 (27th September 2006) - Codes, Liana; Asselah, Tarik; Cazals-Hatem, Dominique; Tubach, Florence; Vidaud, Dominique; Paraná, Raymundo; Bedossa, Pierre; Valla, Dominique; Marcellin, Patrick
Abstract : Background and aims: The rates of fibrosis progression in chronic hepatitis C are significantly different between males and females. The antifibrogenic effect of oestrogen has been proposed, possibly via inhibition of stellate cells. The aim of this study was to evaluate the severity of chronic hepatitis C in women, in relation to the menopause, steatosis and hormone replacement therapy (HRT). Methods: From November 2003 to October 2004, women with chronic hepatitis C were enrolled prospectively. A questionnaire was completed prospectively and a blood sample was obtained on the day of biopsy. We identified characteristics associated with moderate/severe fibrosis using univariate and multivariate analysis. Results: 251 women were included in the study. 122 women (52%) were menopausal and 65 were receiving HRT. 61 (24%) women with moderate/severe fibrosis (F2–F4, Metavir score) had a longer known duration of infection (>15 years), a higher body mass index and presented with steatosis more frequently than 190 (76%) women with mild fibrosis (F0–F1). Women with F2–F4 were more often menopausal (67% v 47%). The probability of fibrosis F2–F4 was lower for menopausal women receiving HRT (p = 0.012). Steatosis was more frequent and more severe in menopausal women. Conclusions: Severity of fibrosis was associated with a longer duration of infection (>15 years), a higher body mass index, advanced steatosis and the menopause. Menopausal women receiving HRT presented with a lower stage fibrosis. These results reinforce the hypothesis of a protective role of oestrogens in the progression of fibrosis. Steatosis may be implicated in the progression of fibrosis after the menopause.